You are on page 1of 5

a.

(p  q)  (r  s) → t

(p  q) (r  s)

p=1 p=0 r=1 r=0

q=1 q=0 q=1 s=1 s=0 s=1


V V V V V V
(p  q)  (r  s) → t

(p  q)  (r  s) = 0 t=1

(p  q)  (r  s)
V

(p  q) = 1 (r  s) = 1

p=1 q=1 r=1 s=1

V V V V
(p  s)  (s  r)  (s  t)

(p  s)  (s  r) = 0 (s  t) = 1
(s  t)
(p  s)  (s  r)
V
s=1
(p  s) (s  r) t = 1

p=0 s=1 s=0 r=1


V V V V
(p  s)  (p  t)  (s  t)  t

(p  s)  (p  t)  (s  t) = 0 t= 1

(p  s)  (p  t)  (s  t) V

(p  s)  (p  t) (s  t)

s=0 t=1
(p  s) = 1
(p  t) V V
p=1 s=1 p=0 t=1
V V V V
(t  (s  r))  ((s  r)  q)

(t  (s  r)) = 0 ((s  r)  q) = 1
V
(t  (s  r)) ((s  r)  q)
t=0 (s  r)=1 (s  r)=0 q=1

(s  r) (s  r) V
s=0 s=0 r=1

V V